Entrepreneurial Behaviour of Dairy Farmers of Jammu Region - Jasbir Singh Manhas , Nafees Ahmad; P.S. Slathia (Indian Journal of Extension Education, 2016)
The study was conducted in R.S. Pura and Akhnoor blocks of Jammu district of Jammu and Kashmir to study the entrepreneurial behaviour of dairy farmers. The study revealed that majority of the respondents i.e., 122 (61.50 percent) possessed medium level of entrepreneurial behaviour, while 23.00 and 15.50 percent had high and low level of entrepreneurial behaviour. The respondents possessed excellent degree of total commitment and immersion followed by self confidence, economic motivation, management orientation and innovativeness. However, respondents had lowest Entrepreneurial Behaviour Index for leadership ability and high tolerance to failure/ ambiguity. The overall Entrepreneurial Behaviour Index for all the categories of selected dairy farmers was 55.03. The overall Entrepreneurial Behaviour Index for small, medium and large dairy farmers was 53.66, 60.73 and 50.73, respectively. A significant difference between different groups of respondents was found with respect to their entrepreneurial behaviour.